Multidimensional strategic outlook on global competitive energy economics and finance - Dinçer, Hasan; Yüksel, Serhat (Bingley, U.K. : Emerald Publishing Limited, 2022)
Economical energy supply is vital for a country's financial success, and factors such as price, continuity, environmental pollution and the country's own energy resources are important contributors. Multidimensional Strategic Outlook on Global Competitive Energy Economics and Finance analyses current trends in energy production and use, with a focus on technological developments that contribute to the reduction of price in energy production and renewable energy sources that provide continuity in energy production and do not emit carbon into the atmosphere. Expanding on the current literature, this book focuses purely on current issues that can increase energy efficiency, while proposing strategies to use energy more effectively and efficiently. The strategies presented in this book will be a significant guide to both academics and industry professionals.
Chapter 1. Identifying new perspectives on geothermal energy investments / Zafer Adali, Hasan Dinçer, Serkan Eti, Alexey Mikhaylov, and Serhat Yüksel -- Chapter2. Theoretical foundations of the relationship between energy investment, monetary conditions, financial development and economic growth / Mafura Uandykova -- Chapter3. Do energy use and environmental pollution cause income? A study on the brics nations / Ramesh Chandra Das and Aloka Nayak -- Chapter 4. Relationship between energy investment and economic growth / Fe Amor Parel Gudmundsson -- Chapter5. The effect of emotional intelligence levels on leadership: An application in the energy sector / Pelin Vardarlier and Murat Al -- Chapter6. Measuring the nonlinearity of the relationship between finance and energy investment / Zaffar Ahmed Shaikh -- Chapter7. Method for assessing the nature of the relationship between energy investment and finance with the criteria of monetary factor thresholds / Tomonobu Sengyu -- Chapter8. Evaluation of the hypothesis of non-linear relationship between finance and energy investment / Mir Sayed Shah Danish -- Chapter9. The impacts of energy usage and economic growth on the ecological footprint and co2 emissions: The case of g-7 countries / Seyma Bozkaya and Mahmut Sami Duran -- -- Chapter10. Assessment of the nature of the relationship between energy investment and finance / Muhammad Safdar Sial -- Chapter11. Importance of renewable energy investments for qualified workforce / Halim Bas, Serkan Eti, and Irfan Ersin -- Chapter12. Is the energy-hungry bitcoin beneficial for portfolio risk reduction? / Yunus Dogaç Arik and Melik Ertugrul -- Chapter13. Bitcoin mining with nuclear energy / Serhat Yüksel, Hasan Dinçer, Çagatay Çaglayan, Gülsüm Sena Uluer, and Anton Lisin.
Includes bibliographical references and index.
Print version record.
Keywords: elektronické knihy; electronic books; Electric power production -- Economic aspects; Business & Economics -- Industries / Energy; Energy industries & utilities